Reducibility of linear systems of difference equations with almost periodic coefficients - Martynyuk, D. I.; Mitropolskiy, Yu. A.; Tynnyi, V. I.; Мартынюк, Д. И.; Митропольский, Ю. А.; Тынный, В. И.; Мартынюк, Д. И.; Митропольский, Ю. А.; Тынный, В. И. (Institute of Mathematics, NAS of Ukraine, 1993)
For the linear systemof difference equations $x(t + 1) = Ax(t) + P(t)x(t)$, where the matrix $P(t)$ is almost periodic, sufficient conditions are given, which reduce it to a system with a constant matrix.